Pengaruh Return On Asset, Debt To Equity Ratio Dan Total Aset Turnover Terhadap Harga Saham PT Ramayana Lestari Sentosa Tbk Periode 2012-2023 - Izzudin, Ahmad; Nuryani, Anum (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Total Asset Turnover on the stock price of PT Ramayan Lestari Sentosa Tbk. The research method used is a quantitative method with an associative approach and the data used is secondary data, namely the financial statements of PT Ramayana Lestari Sentosa Tbk. For 12 (twelve) years that have been made into time series data. Data analysis in this study uses classical assumption tests, multiple regression analysis, hypothesis testing, and coefficient of determination analysis. The results of this study are multiple linear regression equations of Y = -3.041,598 + 97,357X1 + 75,435X2 + 349,385X3. So Return On Assets has a significance value of 0,021. This value is smaller than 0,05. While the calculated t is 2,852, its value is from the t table of 2,306 so that Return On Assets has a significant effect on the stock price variable. While the results of the Debt to Equity Ratio have a significance value of 0,055, the value is greater than 0,05. While for the calculated t 2,245 is smaller than the t table of 2,306 so that this Debt to Equity Ratio does not affect the stock price variable. Same as the Total Assets Turnover, the significance value is only 0,181, which is greater than 0,05 so that the partial significant results on the stock price variable are accepted. But the calculated t 1,463 is rejected because it is smaller than the t table of 2,306. So that Total Assets Turnover has no effect on the stock price. The Stock Price of PT Ramayana Lestari Sentosa Tbk is influenced by Return On Assets (ROA), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) simultaneously during the period 2012–2023, a significance value of 0,013 <0,05 was obtained Keywords: Return On Asset, Debt To Equity Ratio, Total Asset Turnover, Stock Price